2001
DOI: 10.1176/appi.ajp.158.12.2069
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Evidence of Corollary Discharge Dysfunction in Schizophrenia

Abstract: These findings provide direct neurophysiological evidence for a corollary discharge that dampens sensory responses to self-generated, relative to externally presented, percepts in healthy comparison subjects and its failure in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
240
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(284 citation statements)
references
References 12 publications
40
240
4
Order By: Relevance
“…If feedback matches the prediction, the sensory response is suppressed. Electroencephalography and magnetoencephalography (MEG) recordings have shown that auditory cortical responses to self-produced speech are attenuated when compared with responses to tape-recorded speech [1][2][3][4][5]. Similar phenomena are seen in the somatosensory system, where behavioral studies (e.g.…”
mentioning
confidence: 87%
“…If feedback matches the prediction, the sensory response is suppressed. Electroencephalography and magnetoencephalography (MEG) recordings have shown that auditory cortical responses to self-produced speech are attenuated when compared with responses to tape-recorded speech [1][2][3][4][5]. Similar phenomena are seen in the somatosensory system, where behavioral studies (e.g.…”
mentioning
confidence: 87%
“…CD deficits in schizophrenia could arise from the disrupted subcorticalthalamic-cortical circuits that are known to characterize the disease (Andreasen et al 1999). Schizophrenics are impaired in tasks requiring CD (Malenka et al 1986), and their auditory systems show particularly strong evidence for loss of CD-related modulation (Ford et al 2001(Ford et al , 2007. Neurophysiological assessment of CD circuits (e.g., the SC-MD-FEF pathway) could be performed in monkey models of schizophrenia as induced with dopaminergic or glutamatergic drugs (Condy et al 2005, Stone et al 2007 or fetal irradiation (Selemon et al 2005).…”
Section: And Human Diseasementioning
confidence: 99%
“…In particular, masking noise has been shown to reduce stuttering (Maraist and Hutton, 1957), possibly due to the blockade of vocal feedback during speech. Corollary discharge mechanisms (Crapse and Sommer, 2008a,b), like those involved in vocalization-induced inhibition of the auditory cortex, are thought to be involved in the auditory hallucinations of schizophrenia as their absence may interfere with the differentiation between internal and external sources of auditory cortex activity (Ford et al, 2001a;van Lutterveld et al, 2011). Finally, patients with Parkinson's disease exhibit both decreased vocal amplitudes and a smaller magnitude of the Lombard effect (Ho et al, 1999), suggesting a component of their vocal disturbances may be related to the calculation of vocal feedback error in the basal ganglia, in particular the error in vocal amplitude, when presented with masking noise.…”
Section: Further Implications For Vocal Feedback Monitoringmentioning
confidence: 99%